HUBUNGAN ANTARA MINAT BELAJAR DAN KESIAPAN BELAJAR DENGAN PRESTASI BELAJAR GEOGRAFI - Dwi Yuni Astuti; Zulkarnain Zulkarnain; Sugeng Widodo (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research is to find out whether there was a correlation of learning interest and learning readiness with geography achievement at the first year students of SMA Muhammadiyah 2 Bandar Lampung year of 2012-2013. Method of this research was correlation, the population are 181 students and the sample of this research are 75 students. Data collecting technique are test, questionnaire and documentation. Based on the data analysis the result of this research showed that: (1) There was a positive and significance correlation between learning interest with learning Geography achievemnet class X the students of SMA Muhammadiyah 2 Bandar Lampung year of 2012-2013 (: 0.682). (2) There was a positive and significant correlation between physical readiness with learning Geography achievement class X the students of SMA Muhammadiyah 2 Bandar Lampung year of 2012-2013. ( : 0.524). (3) There was a positive and significant correlation between mental readiness with learning Geography achievement class X the students of SMA Muhammadiyah 2 Bandar Lampung year of 2012-2013.( : 0.652).(4) There was a positive and significant correlation between the readiness of the media with learning Geography achievement class X the students of SMA Muhammadiyah 2 Bandar Lampung year of 2012-2013.( : 0.577). Keyword: learning interest, learning readiness and learning achievement